Race differences in the effects of early school behavior problems and substance use type on lifetime arrest - Baker, Thomas (Deviant behavior, 2022)
Early behavior problems may correlate with adult offending. However, the relationship between early problem behavior and lifetime arrests among known offenders has received little empirical examination. In addition, few studies have explored how the associations between early problem behavior and lifetime arrests may differ among Whites and Nonwhites. It is crucial to understand how early problem behavior is associated with lifetime offending given the growing number of interventions targeting early problem behavior that has the promise to interrupt criminal careers. This study begins to explore the relationship between early problem behavior and lifetime arrests using a sample of men and women who were recently incarcerated in New Jersey. Findings suggest that early problem behavior and the usage of various drugs impact lifetime arrests; however, these factors differ between Whites and Nonwhites. Policy implications, limitations, and directions for future research are discussed.